2022
DOI: 10.1080/03007995.2022.2103959
|View full text |Cite
|
Sign up to set email alerts
|

Failed induction of labor and associated factors among women delivered in Jigjiga University Sheik Hassan Yabare Referral Hospital: a cross-sectional study

Abstract: Introduction: Induction of labour is one component of comprehensive obstetrics care services that is increasing employed in modern day obstetrics to decrease the risk of maternal and neonatal morbidity and mortality. However, it has been strongly associated with poor maternal and perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The prevalence of unsuccessful IOL varies worldwide. Previous studies have reported that the prevalence of unsuccessful IOL was 17.3% in Hong Kong [ 23 ], 24.4% in Northwest Ethiopia [ 6 ], and 36.8% in Eastern Ethiopia [ 7 ]. In the current study, the prevalence of unsuccessful IOL was 32.56%, which may have been affected by the patients’ cervical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of unsuccessful IOL varies worldwide. Previous studies have reported that the prevalence of unsuccessful IOL was 17.3% in Hong Kong [ 23 ], 24.4% in Northwest Ethiopia [ 6 ], and 36.8% in Eastern Ethiopia [ 7 ]. In the current study, the prevalence of unsuccessful IOL was 32.56%, which may have been affected by the patients’ cervical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IOL is recommended for pregnancies over 41 weeks of gestation without spontaneous parturition [ 4 , 5 ]. However, unsuccessful IOL occurs in 17.3–36.8% of women [ 6 , 7 ] and is associated with an increased risk of cesarean section and postpartum and neonatal complications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%